Analysis of quantile regression for race time in standard distance triathlons - Zhao, J.; Ma, Y.; Hu, X. (PLOS ONE, 2024)
Purpose This study aims to quantitatively analyze the impact of split times on overall performance in standard distance triathlon events. It also examines how environmental factors such as water type, temperature, and altitude affect overall race outcomes.